Association of Awake Bruxism with Tooth Wear and Occupational Stress Among Mechanical and Non-Mechanical Workers - Fatima Tu Zahra; Syeda Sameen Zehra Rizvi; Amna Riaz; Amna Nisar; Amna Khan; Naveed Ahmad (Pakistan Journal of Medicine and Dentistry)
Background: Awake bruxism, a dental and psychological health concern, is linked to physical and cognitive stress in mechanical workers, while non-mechanical workers may face higher stressors. The purpose of this analysis was to consider the association of awake bruxism with tooth wear and occupational stress in factory workers of Heavy Industries Taxila.